The Cognitive Processes Underlying Event-Based Prospective Memory in School-Age Children and Young Adults: A Formal Model-Based Study - Smith, Rebekah E; Bayen, Ute J; Martin, Claudia (Developmental psychology, 2010)
Fifty children 7 years of age (29 girls, 21 boys), 53 children 10 years of age (29 girls, 24 boys), and 36 young adults (19 women, 17 men) performed a computerized event-based prospective memory task. All 3 groups differed significantly in prospective memory performance, with adults showing the best performance and with 7-year-olds showing the poorest performance. We used a formal multinomial process tree model of event-based prospective memory to decompose age differences in cognitive processes that jointly contribute to prospective memory performance. The formal modeling results demonstrate that adults differed significantly from the 7-year-olds and the 10-year-olds on both the prospective component and the retrospective component of the task. The 7-year-olds and the 10-year-olds differed only in the ability to recognize prospective memory target events. The prospective memory task imposed a cost to ongoing activities in all 3 age groups. (Contains 4 tables, 4 figures and 6 footnotes.)